2023
DOI: 10.1007/s10803-023-05917-8
|View full text |Cite
|
Sign up to set email alerts
|

Moving Together: Social Motor Synchrony in Autistic Peer Partners Depends on Partner and Activity Type

Abstract: Some suggest autistic people display impaired Interpersonal Synchrony. However, partners of different neurotypes can struggle to connect and empathise with one another. We used Motion Energy Analysis to examine Social Motor Synchrony (SMS) in familiar partners of the same neurotype: pairs of autistic and of neurotypical children. Partners played two shared tablet activities, one to support collaboration by facilitating engagement and other-awareness (Connect), and one with no additional design features to faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 80 publications
1
9
0
Order By: Relevance
“…( 86 ), Noel et al. ( 90 ) and Glass and Yuill ( 60 ). Different ROIs have been selected by different groups: Liu et al.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…( 86 ), Noel et al. ( 90 ) and Glass and Yuill ( 60 ). Different ROIs have been selected by different groups: Liu et al.…”
Section: Resultsmentioning
confidence: 99%
“…They involved ASD-ASD and TD-TD children pairs in two joint tablet-based activities and found that the two groups exhibited comparable IMS in the one activity that was not designed to deliberately stimulate interaction, while demonstrating lower IMS in the one activity that was designed to encourage collaboration and other-awareness. Notably, autistic children maintained consistent synchronization levels across both activities, suggesting that in specific social contexts, they may possess comparable or heightened synchronization skills ( 60 ). To our knowledge, only one other study looked at ASD-ASD dyads compared to ASD-TD and TD-TD, but did not find an advantage of neurodevelopmentally homogeneous (over heterogeneous) dyads on IMS ( 86 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations